Singapore Management University launches Financial IT Academy @SMU to train IT professionals in the financial services industry - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Singapore Management University (SMU) has launched the first-of-its-kind academy in Singapore to provide training programmes targeted at the financial services IT segment. The Financial IT Academy @SMU (FITA) will equip financial sector IT professionals with enhanced IT capabilities that are critical to the growth of banking and financial services in Singapore, and also with the essential knowledge of the business needs and processes of financial institutions so that business and IT initiatives can be more effectively integrated for competitive advantage.